2009
DOI: 10.1093/ije/dyp273
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the reduction of relative telomere length over 10 years in the population-based Bruneck Study: introduction of a well-controlled high-throughput assay

Abstract: This is the first comprehensive longitudinal study of individuals who were, on average, 60 at baseline, and who were re-evaluated 10 years later. Our methodology proved to be a reliable tool for a rapid, accurate and cost-efficient determination of RTL with a low amount of DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
125
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 52 publications
16
125
3
2
Order By: Relevance
“…Whereas some earlier, relatively small studies had reported strong inverse association between LTL and mortality (17,41,42), much weaker associations or no association at all was seen in a number of larger, mostly more recent studies (11-13, 25, 26, 43). However, in the so far by far largest study from Denmark with 64,637 participants, with 7607 deaths during 22 years of follow-up, linear graded associations and modestly increased hazards for the shortest versus longest deciles of LTL were seen for all-cause mortality (HR: 1.40, 1.25-1.57), CVD mortality (1.36, 1.12-1.66) and cancer mortality (1.35, 1.11-1.65) (27).…”
Section: Discussionmentioning
confidence: 88%
“…Whereas some earlier, relatively small studies had reported strong inverse association between LTL and mortality (17,41,42), much weaker associations or no association at all was seen in a number of larger, mostly more recent studies (11-13, 25, 26, 43). However, in the so far by far largest study from Denmark with 64,637 participants, with 7607 deaths during 22 years of follow-up, linear graded associations and modestly increased hazards for the shortest versus longest deciles of LTL were seen for all-cause mortality (HR: 1.40, 1.25-1.57), CVD mortality (1.36, 1.12-1.66) and cancer mortality (1.35, 1.11-1.65) (27).…”
Section: Discussionmentioning
confidence: 88%
“…As cell replication generally requires a minimal TL, shortened TL is thought to contribute to senescence (6). Consistent with this, elderly persons with shorter telomeres (in blood) for their age have reduced survival (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 78%
“…To prevent gene loss, shortened telomeres generally activate damage response pathways that cause cell death or impairment of cellular function (2,3). Evidence that cell replication is limited by shorter TL has been reported in vitro (37)(38)(39)(40) through in vivo experimentation in animal models (41)(42)(43) and in cross-sectional and longitudinal observational studies (7)(8)(9)(10)(11)(12)(13)(44)(45)(46)(47)(48). On the other hand, whether inherited TL alters the risks of developing cancer is unsettled (20,21,(49)(50)(51)(52)(53), so the implications of the association of paternal ages at reproduction with TL for cancer risk are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cross-sectional studies are abundant, there have been very few longitudinal studies of telomere length [Aviv et al, 2009;Ehrlenbach et al, 2009;Epel et al, 2009;Nordfjall et al, 2009;Farzaneh-Far et al, 2010]. One consistent finding from the published longitudinal data is that the rate of telomere length change over time is inversely related to the baseline telomere length [Aviv et al, 2009;Farzaneh-Far et al, 2010].…”
Section: Future Directionsmentioning
confidence: 99%